Jonathan Miller : custom energy bar entrepreneur pitches sharks - Shein, James B., 1942- (SAGE knowledge. Cases., 2016)
Jonathan Miller appeared in September 2009 on 'Shark Tank', the ABC television reality show featuring entrepreneurs versus angel investors in a discussion of the business value proposition and to win a negotiation for an investment from one of the 4 Sharks. The company he founded, Element Bars, a maker of custom energy bars, needed investment capital. Prior to appearing on the show, Miller had considered several financing options available to entrepreneurs: loans and other debt capital and equity capital, each of which are evaluated in the case.